NUZUM AL-DURAR FI TANASUB AL-AYATI WA AL-SHUAR (Tinjauan Metode dan Pendekatan Tafsir) - Rasyad, Rasyad (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2019)
Tafsir al-Qur'an has had a series of its own history by involving several important figures in it. The commentators have played an active role in contributing their thoughts and ideas in exploring and revealing the treasures of knowledge contained in the Qur'an. That is why interpretation continues to grow rapidly from time to time, and from generation to generation, using a variety of methods and approaches. Al-Biqa'y is one of the commentators, and his commentary is